ANALISIS FINANCIAL DISTRESS DENGAN METODE ALTMAN Z – SCORE PADA PERUSAHAAN HOTEL YANG TERDAFTAR DI BEI - Wulansari, Murwani (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
The purpose of this study was to determine the business continuity of PT. Eastparc Hotel Tbk, PT. Bukit Uluwatu Village Tbk and PT. Hotel Sahid International Tbk uses secondary data in the form of financial statements for 2019 – 2021. This study uses the Altman Z Score method which is one method for assessing the bankruptcy of a company. The covid 19 pandemic caused a significant decrease in performance at PT. Bukit Uluwatu Village Tbk Z. Z Score PT. Bukit Uluwatu Village Tbk in 2020 was -2,91, it decreased from 0,35 in 2019. Such conditions indicate that PT. Bukit Uluwatu Village Tbk experienced financial distress